Gastrointestinal bleeding caused by epitheloid sarcoma: a case report - Lee, Fei Yee; Lim, Limi; Gee, Tikfu (Malaysian Medical Association, 2016)
Epithelioid sarcoma (ES) of the small bowel is a rare gastrointestinal tumour. We report a case of gastrointestinal bleeding secondary to small bowel ES in a 55-year-old gentleman. After gastroscopy and colonoscopy failed to identify the source of bleeding, we proceeded with computed tomography angiogram of the mesentery, which revealed intraluminal blood clot in the distal jejunum with features of obstruction. This is a rare cause of obscure gastrointestinal bleeding and emphasises the need for additional evaluation in the presence of negative endoscopic findings.